2002
DOI: 10.3758/bf03195291
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the output monitoring component of event-based prospective memory performance

Abstract: The goal of this study was to augment the standard event-based prospective memory paradigm with an output monitoring component. That component involves memory for past actions and, in the context of prospective memory, is largely responsible for repetition and omission errors. The modified paradigm also provides an index of what people believe to be true concerning their past prospective memory performance. More elaborate prospective responses decreased forgetting that an intention had been fulfilled, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 24 publications
1
41
1
Order By: Relevance
“…On the basis of the differences in the cue interference measure, a future endeavor will be to delineate individual differences in the retrieval processes that occur when participants notice an event-based cue. Studies in which output monitoring has been capitalized on would be a good starting point, because there difficulty of the retrieval component of prospective memory has been manipulated (e.g., Marsh, Hicks, Hancock, & Munsayac, 2002). In these studies, participants typically have to give a new response each time they detect a different event-based cue.…”
Section: Author Notementioning
confidence: 99%
“…On the basis of the differences in the cue interference measure, a future endeavor will be to delineate individual differences in the retrieval processes that occur when participants notice an event-based cue. Studies in which output monitoring has been capitalized on would be a good starting point, because there difficulty of the retrieval component of prospective memory has been manipulated (e.g., Marsh, Hicks, Hancock, & Munsayac, 2002). In these studies, participants typically have to give a new response each time they detect a different event-based cue.…”
Section: Author Notementioning
confidence: 99%
“…In the real world, such detection does not necessarily mean that the intention will be fulfilled. Rather, the cue can set in motion a whole other set of cognitive processes, including verification that this is the correct opportunity to respond, any additional coordination processes associated with temporarily suspending the current task at hand (see, e.g., Marsh, Hicks, Cook, Hansen, & Pallos, 2003), and, finally, a whole set of outputmonitoring processes that can be used to avoid making repetition and omission errors (e.g., Einstein, McDaniel, Smith, & Shaw, 1998;Marsh, Hicks, Cook, & Mayhorn, in press;Marsh, Hicks, Hancock, & Munsayac, 2002).…”
mentioning
confidence: 99%
“…The study of prospective memory investigates aspects of intention formation and intention completion (Marsh, Hicks, Hancock, & Munsayac, 2002). Examination of prospective memory by Einstein, McDaniel, Smith, and Shaw (1998) revealed that the performance of a prospective memory task can also depend on output monitoring.…”
Section: Takashi Kusumimentioning
confidence: 99%